Patricia Hill Collins : reconceiving motherhood - Story, Kaila Adia, 1980- (Demeter Press, 2014)
Patricia Hill Collins has given new meaning to the institution of motherhood throughout her publishing career. Introducing scholars to new conceptions, such as, othermothering and mothering of mind, Collins through her creative and multifaceted analysis of the institution of motherhood, has in a large sense, reconceived what it means to be a mother in a national and transnational context. By connecting motherhood as an institution to manifestations of empire, racism, classism, and heteronormativity, Collins has informed and invented new understandings of the institution as a whole. This anthology explores the impact/influence/ and/or importance of Patricia Hill Collins on motherhood research, adding to the existing literature on Motherhood and the conceptions of Family. In addition, this collection raises critical questions about the social and cultural meanings of race, class, gender, sexual orientation, and mothering.--